Answer:
![p(x) = -5x^3 -6x^2 + 3x + 1](https://img.qammunity.org/2023/formulas/mathematics/college/1n2kagzkq0f7oza6sxy28i8hihicy94wk9.png)
Explanation:
Given cubic function:
![p(x) = ax^3 + bx^2 + cx + d](https://img.qammunity.org/2023/formulas/mathematics/college/w8mx2evxb1psysnya46161rjq7vs9hh8jz.png)
As point (0, 1) is on the curve, substitute x = 0 into the function, set it to 1, and solve for d:
![\begin{aligned} p(0) & = 1\\ \implies a(0)^3 + b(0)^2 + c(0) + d & = 1\\ \implies d & = 1 \end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/4qzhju9zu84ndfa5bxqgu08mc9qu6plvjx.png)
Differentiate the function:
![\begin{aligned} p(x)& = ax^3 + bx^2 + cx + d\\\implies p'(x)&=3 \cdot ax^(3-1)+2 \cdot bx^(2-1)+1 \cdot cx^(1-1)+0 \\p'(x)&=3ax^2+2bx+c\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/sw6mxa2mfiw95geuq7inx34awujs04y5mt.png)
The tangent equation at the point (0, 1) is y = 3x + 1.
Therefore, the gradient of the tangent equation when x = 0 is 3.
To find the gradient of the function at a given point, substitute the x-value of that point into the differentiated function. Therefore, substitute x = 0 into the differentiated function, set it to 3, and solve for c:
![\begin{aligned}p'(0) & =3 \\ \implies 3a(0)^2+2b(0)+c & =3\\ \implies c & = 3\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/895y5jbqn6gqdy5kk4wnlror4f87pnsbe2.png)
Substitute the found values of c and d into the function:
![p(x) = ax^3 + bx^2 + 3x + 1](https://img.qammunity.org/2023/formulas/mathematics/college/hoqlv4qrduh662wgz96mugzgfvigwmarn2.png)
Substitute point (-1, -3) into the function and solve for b:
![\begin{aligned}p(-1) & = -3\\\implies a(-1)^3 + b(-1)^2 + 3(-1) + 1 & = -3\\-a+b-3+1&=-3\\-a+b&=-1\\b&=a-1\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/ekv1qnhxey8zgw2hwypbulj9f3pvol8bed.png)
To find the turning points of a function, set the differentiated function to zero and solve for x.
As there is a turning point of function p(x) when x = -1, substitute x = -1 into the differentiated function and set it to zero (remembering to substitute the found value of c = 3 into the differentiated function):
![\begin{aligned} p'(-1) & =0\\\implies 3a(-1)^2+2b(-1)+3 & = 0\\3a-2b+3&=0\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/sbw9qe3hvvazvsu2f8whhitq6ae1ojw5xe.png)
Substitute the found expression for b into the equation and solve for a:
![\begin{aligned}3a-2b+3&=0\\\implies 3a-2(a-1)+3&=0\\3a-2a+2+3&=0\\a+5&=0\\a&=-5\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/ytmysk15jr0er9th2mpbece2dzkity36em.png)
Finally, substitute the found value of a into the found expression for b and solve for b:
![\begin{aligned}b & = a-1\\\implies b & = -5-1\\b & = -6\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/2i5km8dix8a4b3le4h6btdjsbvz0wz2qeb.png)
Therefore:
Differentiation Rules
![\boxed{\begin{minipage}{4.8 cm}\underline{Differentiating $ax^n$}\\\\If $y=ax^n$, then $\frac{\text{d}y}{\text{d}x}=nax^(n-1)$\\\end{minipage}}](https://img.qammunity.org/2023/formulas/mathematics/college/jd9yulc9ok9s5ihxu08u0mey6xjdl9zpkr.png)
![\boxed{\begin{minipage}{4cm}\underline{Differentiating a constant}\\\\If $y=a$, then $\frac{\text{d}y}{\text{d}x}=0$\\\end{minipage}}](https://img.qammunity.org/2023/formulas/mathematics/college/cu1jn5ujbfmz8g1rppx5wsbch6rrkr30ie.png)